Piloting a cancer awareness app across six European countries: a pre-post study - Ahmed, Furqan; Romero Saletti, Silvana Melissa; D’Souza, Erica; Espina, Carolina; Ritchie, David; Barceló, Ana Molina; Carbó, Marina Pinto; Cervera, Paula Romeo; Seum, Teresa; Brenner, Hermann; Van den Broucke, Stephan; Krini, Maria; et al. (Frontiers in Public Health, 2025)
BackgroundCancer remains a significant public health challenge in Europe, accounting for over 22% of global cancer cases. Mobile health applications may help to increase the awareness of cancer risks and preventive behaviors. However, usability barriers and disparities in digital health literacy (DHL) may limit their impact.ObjectiveThis study evaluated the usability of the EU Mobile App for Cancer Prevention and changes in cancer awareness associated with use across six European countries (Cyprus, Germany, Hungary, Portugal, Slovenia, Spain), focusing on variations by DHL and sociodemographic factors.MethodsA pre-post design was employed, combining pre- and post-usage surveys (N = 328 pre; n = 77 post). Participants interacted with the app for 7 days. Usability was assessed via the System Usability Scale (SUS), cancer awareness via an 18-item quiz, and DHL using the eHEALS tool. Descriptive statistics summarized key variables, while t-tests and ANOVAs assessed group differences in usability and cancer awareness outcomes.ResultsA total of 328 participants completed the pre-usage survey, with 77 proceeding to the post-usage phase; the primary reason for dropout was technical difficulties. The app’s overall usability was rated as moderate (Mean = 62.56 on the SUS) and did not differ significantly across demographic or usage subgroups. Cancer awareness scores improved from 50.45 to 53.31 (p < 0.001) showing significant moderate improvement, particularly among those with lower DHL and higher education. We observed no dose response relationship between self-reported app usage (frequency or session duration) and changes in cancer awareness.ConclusionThis pilot study demonstrates that the EU Mobile App for Cancer Prevention can enhance cancer awareness, while currently the usability was judged to be moderate. Targeted refinements in navigation, setup procedures, and content tailoring for low-DHL users are essential to improve engagement and ensure equitable reach.